Implementasi Total Quality Managemen di SMPIT Abu Bakar Yogyakarta dan Implikasinya Terhadap Prestasi Sekolah - Akhsanul Fuadi (Universitas Alma Ata, 2020)
Implementation of Total Quality Management is absolutely necessary to be implemented in school to increase schools achievement . Total Quality Management is implemented by SMPIT Abu Bakar Yogyakarta as a strategy to increase a progressive achievements at the SMPIT Abu Bakar Yogyakarta. This management is implemented to every aspects to realize the progressive achievements and never stop.The results of the implementation of the